OPTIMISASI PENJADWALAN KEDATANGAN TRUK EKSTERNAL DI TERMINAL PETI KEMAS KOJA MENGGUNAKAN DYNAMIC COLLABORATIVE TRUCK APPOINTMENT SYSTEM (DCTAS) - Alissia Jasmine, Putri
Koja Container Terminal is a subsidiary of PT. Pelabuhan Indonesia II that provides loading and unloading services for containers at Tanjung Priok Port. In 2022, Koja Container Terminal experienced a decrease in market share by 0.60% from 2021 to 2022. Based on the of the 5 whys analysis, the main cause of this issue is the lack of agreed-upon arrival schedules for external trucks between the terminal and trucking companies. Therefore, the proposed solution in this research is to create agreed-upon arrival schedules for external trucks between the terminal and trucking companies. The approach used in this research is the Dynamic Collaboration Truck Appointment System (DCTAS). DCTAS utilizes two models, namely the integer linear programming model and Discrete Event Simulation (DES). The integer linear programming model is used to create arrival schedules for external trucks that minimize the total cost of external truck congestion. The Discrete Event Simulation (DES) model is used to determine the turnaround time for external trucks before and after the optimal schedules are determined. Based on the linear programming and simulation models conducted, the turnaround time for imported external trucks is found to be 44.5 minutes, and for exported external trucks, it is 42.19 minutes. The turnaround time for imported and exported external trucks using DCTAS is faster compared to the turnaround time without using DCTAS. There is a decrease of 17.14% for the turnaround time of imported external trucks and 51.68% for the turnaround time of exported external trucks.